The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/0074-0276108022013023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a modified shell vial culture procedure with conventional mouse inoculation for rabies virus isolation

Abstract: Rabies is a neurotropic disease that is often lethal. The early diagnosis of rabies infection is important and requires methods that allow for the isolation of the virus from animals and humans. The present study compared a modified shell vial (MSV) procedure using 24-well tissue culture plates with the mouse inoculation test (MIT), which is considered the gold standard for rabies virus isolation. Thirty brain samples (25 positive and 5 negative by the fluorescent antibody test) obtained from different animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The T3 protocol (three passages of 48h each) failed in detecting one positive sample in BHK-21 cells and two in N2A. Previous studies have suggested a minimal incubation period of three (ANTÚNEZ et al, 2013) or 4-5 days (RUDD & TRIMARCHI, 1989), while others suggested that a 24h period would be adequate (BOURHY et al, 1989;CHITRA et al, 1988). These discrepancies may reflect different VI protocols or cells (cell lines, passage number, etc.…”
Section: ---------------Vi 1 In N2a Cells/protocol ------------------mentioning
confidence: 97%
See 1 more Smart Citation
“…The T3 protocol (three passages of 48h each) failed in detecting one positive sample in BHK-21 cells and two in N2A. Previous studies have suggested a minimal incubation period of three (ANTÚNEZ et al, 2013) or 4-5 days (RUDD & TRIMARCHI, 1989), while others suggested that a 24h period would be adequate (BOURHY et al, 1989;CHITRA et al, 1988). These discrepancies may reflect different VI protocols or cells (cell lines, passage number, etc.…”
Section: ---------------Vi 1 In N2a Cells/protocol ------------------mentioning
confidence: 97%
“…Hence, virus isolation (VI) in cell culture has been proposed as an alternative method to replace MIT as a confirmatory test for rabies. Isolation systems based on mouse neuroblastoma (N2A) and baby hamster kidney (BHK-21) cells have been evaluated regarding to sensitivity to RabV from different animal species (RUDD et al, 1980;1989;RUDD & TRIMARCHI, 1987;ANTÚNEZ et al, 2013). Considering the fastidious growth and the special culture medium requirements for N2A cells, the use of BHK-21 cells for VI as confirmatory rabies diagnosis would compare favorably since BHK-21 cells display a fast growth in vitro and are largely used in many laboratories.…”
Section: Subsequentemente Essas Amostras Foram Submetidas a Três Promentioning
confidence: 99%